2022
DOI: 10.3390/medicina58050619
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in a Cohort of Patients Who Underwent Double-J Ureteric Stenting—A Single Center Experience

Abstract: Background and Objectives: Minimally invasive procedures, such as double-J ureteric stenting, could be a promising therapeutic alternative to conservative management of obstructive urinary tract pathology. We aimed to evaluate the safety and effectiveness of double-J ureteric stenting in pregnant women with ureterohydronephrosis or urolithiasis, along with their infectious complications, and to assess the pregnancy outcomes of this cohort of patients in comparison with a control group. Materials and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Reflux pyelonephritis can be a serious complication that can quickly lead to urosepsis in the absence of adequate antibiotic treatment [30]. However, as in other studies [28,31], the incidence of symptoms associated with double-J catheters in our study was much lower than the nearly 80% reported in other studies [13,25]. We did not find, as reported in other studies [32], that multiple ESWL sessions are required in patients with double-J stents to achieve the same effect as in patients without stents.…”
Section: Discussionmentioning
confidence: 92%
“…Reflux pyelonephritis can be a serious complication that can quickly lead to urosepsis in the absence of adequate antibiotic treatment [30]. However, as in other studies [28,31], the incidence of symptoms associated with double-J catheters in our study was much lower than the nearly 80% reported in other studies [13,25]. We did not find, as reported in other studies [32], that multiple ESWL sessions are required in patients with double-J stents to achieve the same effect as in patients without stents.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the time interval between the onset of urinary symptoms and hospital admission for further investigations was higher for patients with urosepsis compared to patients with uncomplicated UTIs. All these are known risk factors for developing UTIs in pregnancy [6,51], and we hypothesize that the longer timeframe until admission to the urology department in the case of patients with urosepsis constitutes an important aggravating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors and physiologic changes in pregnancy play an important role in the development and spread of UTIs. The current literature has identified as predisposing factors for UTIs the following: ethnicity, advanced maternal age, multiparity, hydronephrosis in pregnancy, personal history of UTI, immunosuppressive conditions (e.g., diabetes mellitus), anemia, smoking, and low educational level or socioeconomic status [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We found no maternal deaths in either group. However, despite the efficacy and safety of urologic maneuvers [37], complications and increased incidence of fetal distress and the need for transfer to a maternity hospital should not be neglected. In contrast, pregnant women without urosepsis did not experience fetal distress requiring transfer [14].…”
Section: Discussionmentioning
confidence: 99%